An objective assessment of toddlers’ physical activity and sedentary levels: a cross-sectional study - Vanderloo, Leigh M. (BMC Public Health, 2015)
BACKGROUND: Little evidence exists on the physical activity and sedentary time of Canadian toddlers; this study objectively measured such behaviors and compared participants’ activity levels to national guidelines. Levels of screen-viewing among toddlers were also explored. METHODS: Forty toddlers (mean age = 25.7 months) wore Actical accelerometers for seven consecutive days (15 s epoch). Parents/guardians completed a wear-time log and a demographic and screen-viewing questionnaire. Descriptive analyses were used to determine participants’ levels of physical activity and sedentary time, to identify whether toddlers were meeting physical activity/sedentary guidelines, and to explore demographic variables. T-tests were used to assess whether toddlers’ activity levels differed based on cut-points applied and various demographic and screen-related variables. Regression analyses were conducted to examine associations between toddlers’ sedentary time and screen-viewing levels. RESULTS: Toddlers engaged in 37.27 (SD = 3.79) to 49.40 (SD = 3.29) mins/hr of sedentary time, 9.79 (SD = 2.90) to 18.78 (SD = 3.22) mins/hr of light-intensity physical activity (LPA), 0.82 (SD = 0.72) to 3.95 (SD = 1.93) mins/hr of moderate- to vigorous-intensity physical activity (MVPA), and 10.60 (SD =3.29) to 22.73 (SD = 3.97) mins/hr of total physical activity (TPA), based on the Trost et al. and the Canadian Health Measures Survey (CHMS) cut-points respectively; these rates were significantly different (p <.001). On at least 1 day, 17.5 % (Trost et al. cut-points) and 97.5 % (CHMS cut-points) of the sample met or exceeded the Canadian physical activity guidelines. No statistically significant differences in sedentary time or physical activity (all intensities) based on sex were reported (p <.001); however, LPA (CHMS cut-points) did significantly differ based on childcare attendance (p <.05). Approximately 93.2 % of participants watched television, and 56.8 % utilized computers. Only 18.8 and 25.0 % of children under 2 years and 70.8 and 62.5 % of 2–3 years olds met the screen-use recommendation of the sedentary behavior guidelines on weekdays and weekend days, respectively. DISCUSSION AND CONCLUSION: The implications of this work suggest that a greater understanding of toddlers’ activity patterns is needed; additional mechanisms of promoting active behaviors among this group should be explored.